`No pain, no gain`: former elite female gymnasts` engagements with pain and injury discourses - Tynan, R.; McEvilly, N. (Qualitative Research in Sport, Exercise and Health, 2017)
This paper investigates former elite female gymnasts` views and experiences of pain and injury. The purpose of the study was to examine how participants engaged with pain and injury discourses and interrogate the ways in which certain knowledge and practices had become dominant. A Foucaultian theoretical framework underpinned the study, making use of Foucault`s work on discourses, power and resistance. Data were generated through semi-structured interviews with seven former elite gymnasts. By analysing the participants` talk through poststructural discourse analysis, three themes were identified. Firstly, participants` persistence through pain and injury was due to the desire to compete. Secondly, participants differentiated between `good pain` and `bad pain`. Thirdly, participants had a higher tolerance for pain than for injury. This research raises questions about the dominance of a `no pain, no gain` discourse, and the ways in which gymnasts may develop an uncritical acceptance of particular `truths` surrounding pain and injury.